All Days 2012
DOI: 10.2118/163352-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Shale Swelling in Water-Based Muds

Abstract: Historically, shale instability is a challenging issue when drilling reactive formations using water-based muds (WBM). Shale instability leads to shale sloughing, stuck pipe, and shale disintegration causing an increase in fines that affects the rate of penetration. To characterize shale instability, laboratory tests including Linear Swell Meter (LSM), shale-erosion and slake-durability are conducted in industry. These laboratory tests, under different flow conditions, provide shale-fluid interaction parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…4(a). It was observed that the prediction accuracy with ANN has significantly improved in comparison to earlier empirical models (Kulkarni et al 2012).…”
Section: Ann Modeling For a (Saturation Swelling Parameter)mentioning
confidence: 82%
“…4(a). It was observed that the prediction accuracy with ANN has significantly improved in comparison to earlier empirical models (Kulkarni et al 2012).…”
Section: Ann Modeling For a (Saturation Swelling Parameter)mentioning
confidence: 82%
“…They employed various inputs, such as clay content, applied pressures, and fluid composition, to predict swelling behavior. Similarly, Kulkarni et al 53 proposed a model to estimate the swelling of shale by including the shale's cation exchange capacity (CEC) and the concentrations of NaCl salt in the drilling fluid. Maghrabi et al 7 constructed an ANN model specifically for forecasting shale swelling in WBDFs.…”
Section: Introductionmentioning
confidence: 99%
“…The ANN approach has also been used to characterize other properties of the drilling fluids (e.g., filtration properties [Jeirani and Mohebbi 2006]). Recent work has demonstrated shale swelling modeling based on the ANN approach ) as well as using other numerical models (Kulkarni et al 2012;.…”
Section: Introductionmentioning
confidence: 99%